Pengaruh Gaya Kepemimpinan Reward, Lingkungan Kerja Dan Komitmen Organisasi Terhadap Kinerja Karyawan Di Bkd Malang - Rohiyah Rohiyah; Hadi Sunaryo; M. Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThe purpose of this study is to examine the influence of Leadership Style, Reward, Work Environment and Organizational Commitment on Employee Performance in the Regional Civil Service Agency of Malang. This research uses descriptive type. The data used are primary and secondary data obtained using a questionnaire by taking a population sample of 44 (forty four) respondents.               This study uses analytical tools such as Validity, Reliability, Normality, Multiple Regression Tests, Multicollinity Tests, Heteroscedasticity Tests, F Tests, and t Tests and is measured using a Likert scale. Where the results of the analysis depend on the score obtained from respondents.        The results of this study are (1) Leadership Style has a positive and significant effect on employee performance (2) Reward has a positive and significant effect on employee performance (3) Work Environment has a positive and significant effect on employee performance (4) Organizational Commitment has no effect on employee performance . Keywords : Leadership Style, Reward, Work Environment, Organizational                   Commitment, Performance.